Edukasi Karang Taruna Putri Surya Muda Mengenai Pengaruh Menstruasi Terhadap Anemia - Wahyuni Wahyuni; Muhammad Andre Agasi; Felani Hilmi Azahra; Wahyu Tri Sudaryanto; Dinda Rispati (Universitas 45 Surabaya, 2023)
Anemia is defined as a disease that occurs due to a reduction in red blood cells or erythrocytes in the human body. One of the causes of a lack of red blood cells or erythrocytes is excessive menstrual bleeding, a condition like this is experienced by many young women. Anemia can cause sufferers to experience symptoms such as weakness, weakness, tiredness, weakness and lethargy. The counseling was aimed at members of Karang Taruna Surya Muda using educational methods through poster-based media on the topic of the Effect of Menstruation on Anemia. Members of Karang Taruna Surya Muda were given a pre test before the counseling was carried out, and also a post test after the counseling was carried out. This aims to evaluate the level of knowledge of the extension topic. Based on the results of the paired sample T test, it can be concluded that there is a significant difference, namely an increase in the knowledge of young women at Karang Taruna Surya Muda before and after socializing the effect of menstruation on anemia.